Early poststroke clinically significant fatigue predicts functional independence: a prospective longitudinal study - Juárez-Belaúnde, Alan; Soto-León, Vanesa; Dileone, Michele; Orcajo, Elena; León-Álvarez, Natacha; Muñoz, Alberto; Tornero, Jesus; Oliviero, Antonio (Frontiers in Neurology, 2024)
Background: Post-stroke fatigue is a prevalent issue among stroke survivors, significantly impeding functional recovery and diminishing their quality of life.This prospective cohort study aims to investigate the association between post-stroke fatigue and the extent of functional recovery in survivors of ischemic and haemorrhagic strokes. Additionally, it seeks to delineate the temporal progression of post-stroke fatigue in these two stroke subtypes.We assessed a cohort of 79 patients recovering from acute ischemic or haemorrhagic strokes. Post-stroke fatigue was quantified using the Fatigue Severity Scale (FSS) and Numeric Rating Scale (NRSfatigue). Patients' condition was evaluated using the National Institute of Health Stroke Scale (NIHSS), and functional independence levels were determined using the Barthel Index for Activities of Daily Living (BIADL), and the Modified Rankin Scale (MRS).Depressive mood and pain were measured using the Beck Depression Inventory (BDI) and Numeric Rating Scale for pain (NRSpain), respectively.Results: Our primary findings indicate that the early manifestation of clinically significant fatigue (CSF) is predictive of a poorer trajectory in functional independence levels during recovery. Furthermore, we observed differing patterns of fatigue progression between ischemic and haemorrhagic strokes. Fatigue tends to ameliorate over time in haemorrhagic stroke cases, paralleling functional recovery, while it remains stable over time in ischemic stroke cases.Our results underscore the detrimental impact of early post-stroke fatigue on long-term outcomes. Furthermore, they highlight the imperative for managing post-stroke fatigue, particularly during the subacute phase of stroke recovery.